Impacts of Plant-derived Secondary Metabolites for Improving Flora in Type 2 Diabetes - Li, Lin Z.; Yan, Yan; Song, Qinghe; Wang, Zhibin; Zhang, Wei; Hou, Yanli; Zhang, Xiandang (Current Diabetes Reviews, 2023)
Background: Diabetes has become a problem that plagues public healthcare systems. Recent studies have shown that intestinal flora exerts positive therapeutic effects on metabolic diseases, and plant-derived secondary metabolites are safe, effective and easy to prepare and also have an impact on intestinal flora and diabetes; these drugs have rarely been reviewed before as a class of drugs for diabetes, especially focusing on the intestinal flora. Therefore, studying the relationship between plant-derived secondary metabolites and diabetes mellitus is crucial. Objective: The objective of this study is to summarize and investigate the therapeutic mechanism of drugs extracted from natural plants effects on type 2 diabetes mellitus. Methods: The relationship between flora and type 2 diabetes was investigated by reviewing the recent experimental literature, and the pathways available for natural plant-derived secondary metabolites in the treatment of type 2 diabetes were summarized. Results: The therapeutic mechanisms of common plant-derived secondary metabolites for type 2 diabetes were summarized with a focus on the prebiotic efficacy of natural plant-derived secondary metabolites and the modulation of intestinal flora, and the mechanisms through which plantderived secondary metabolites treat type 2 diabetes via effects on intestinal flora are further reviewed. Conclusion: Common plant-derived secondary metabolites can play a role in regulating bacteria in the intestinal tract by enriching beneficial bacteria and removing harmful bacteria to achieve their therapeutic effect on type 2 diabetes. In addition, due to their excellent ability to regulate intestinal flora, plant-derived secondary metabolites may also have excellent efficacy in cancer and obesity, among other diseases.
Keywords: antibacterial